Examining the relationship between obesity and mental health outcomes among individuals admitted to a level I trauma centre. Issue 5 (31st July 2018) - Reynolds, M.; Driver, S.; Bennett, M.; Patel, S.; Rainey, E.; Warren, A. M.
Summary: The increased incidence of obesity in the general population translates into clinicians caring for an increased number of trauma patients with obesity. Previous research has documented the unique anatomical and physiological challenges that clinicians face when caring for trauma patients with obesity; however, little is known about psychological challenges that trauma patients with obesity may also experience in the months following injury. The aim of this study is to determine the relationship between obesity and (i) mental health, (ii) demographic and injury‐related variables and (iii) quality‐of‐life outcomes among trauma patients between hospitalization and 3‐months post‐injury. This is a prospective, longitudinal study conducted between March 2012 and May 2014 at a single, level I trauma centre in the southwest United States. Inclusion criteria for this convenience sample consisted of patients who were admitted to the trauma or orthopaedic trauma service ≥24 h, medically stable, spoke English or Spanish and ≥18 years of age. In total, 455 eligible patients were consented and enrolled; 343 (70.87%) completed 3‐month follow‐up. The objective of this study is to investigate the relationship between obesity and mental health among trauma patients in the months following injury. Demographic and injury‐related data were also collected; patients' height and weight were used to determine body mass index. Health outcomes were assessed during initial hospitalization and at 3‐month follow‐up and included depression, post‐traumatic stress symptoms, pain and return to work. Prior to data collection, it was hypothesized that obesity would have a negative effect on mental health outcomes among patients 3 months post‐injury. The final sample consisted of 343 participants; average age was 46.4 ± 17.3 years; majority male ( n = 213, 63%) and Caucasian ( n = 231, 69%). Patients with obesity had higher odds of screening positive for depression (odds ratio [OR] = 2.36, P = 0.02) and overweight patients had lower odds of returning to work (OR = 0.31, P = 0.01) 3 months post‐injury compared to patients of normal weight (65% vs. 40%). No other significant differences were found. Results of the current study are novel in that they identify psychological challenges that overweight and trauma patients with obesity may experience. These results demonstrate the need for mental health professionals to be involved in follow‐up care to extending in the months following injury.